Orthodontic Management of Congenitally Missing Maxillary Lateral Incisors: A Case Report - Sergio Paduano; Iacopo Cioffi; Roberto Rongo; Antonello Cupo; Rosaria Bucci; Rosa Valletta (Hindawi Limited, 2014)
This case report describes the orthodontic treatment of a woman, aged 15 years, with permanent dentition, brachyfacial typology, with congenitally missing maxillary lateral incisors. Multibracket straightwire fixed appliance was used to open the space for dental implant placement, and treat the impaired occlusion. The missing lateral incisors were substituted with oral implants.